Bioanalytical method for in vitro metabolism study of repaglinide using 96-blade thin-film solid-phase microextraction and LC–MS/MS. (January 2015) - Simões, Rodrigo Almeida; Bonato, Pierina Sueli; Mirnaghi, Fatemeh S; Bojko, Barbara; Pawliszyn, Janusz
Background: A high-throughput bioanalytical method using 96-blade thin film microextraction (TFME) and LC–MS/MS for the analysis of repaglinide (RPG) and two of its main metabolites was developed and used for an in vitro metabolism study.Results: The target analytes were extracted from human microsomal medium by a 96-blade-TFME system employing the low-cost prototype 'SPME multi-sampler' using C18 coating. Method validation showed recoveries around 90% for all analytes and was linear over the concentration range of 2–1000 ng ml -1 for RPG and of 2–500 ng ml -1 for each RPG metabolite.Conclusion: The method was applied to an in vitro metabolism study of RPG employing human liver microsomes and proved to be very useful for this purpose.